2015
DOI: 10.1111/clr.12632
|View full text |Cite
|
Sign up to set email alerts
|

Short implants compared to implants in vertically augmented bone: a systematic review

Abstract: This evidence should, however, be interpreted with caution as it is derived from four RCT's with limited sample size (ranging from 15 to 30 per group), limited follow-up and performed by the same research group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
92
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(97 citation statements)
references
References 25 publications
3
92
0
2
Order By: Relevance
“…The use of such implants can reduce treatment time, cost, and postoperative morbidity compared to bone augmentation procedures. The first EAO consensus conference (2006) had defined short implants as a device with a design intrabony length of 8 mm or less [21] and had demonstrated high success rates and predictable clinical outcomes for placement of short implants [1214], but there were still controversies regarding the long-term consequences of peri-implant bone loss around short implants and its impact on the long-term implant success rate at that time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of such implants can reduce treatment time, cost, and postoperative morbidity compared to bone augmentation procedures. The first EAO consensus conference (2006) had defined short implants as a device with a design intrabony length of 8 mm or less [21] and had demonstrated high success rates and predictable clinical outcomes for placement of short implants [1214], but there were still controversies regarding the long-term consequences of peri-implant bone loss around short implants and its impact on the long-term implant success rate at that time.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies have demonstrated high success rates and predictable clinical outcomes for placement of short implants. Short implants have been proposed as an alternative to avoid the problems associated with vertical augmentation [1214]. Still, there is a need for more clinical studies to support this recent concept.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, results from previous studies on narrow-diameter implants indicate a survival rate of between 96% and 99.4% with follow-ups of 1-5 years and irrespective of the surgical approach used (two-stage surgical approach, one-stage surgical approach, or immediate-function approach; 6,[15][16][17]. However, the limited sample size (12,17) and follow-up duration (12,15) of these studies may increase potential bias, obscuring the true outcomes of fixedprosthetic rehabilitations supported by narrow-diameter or short-length implants.…”
Section: Introductionmentioning
confidence: 99%
“…The use of short implants (7-8.5 mm) has been associated with lower success rates (11), which were nevertheless comparable to those of implants placed in vertically augmented bone (12). In the literature, the reported survival rates for short dental implants range widely (between 88% and 100%; 2,13,14).…”
Section: Introductionmentioning
confidence: 99%
“…3 Sloping shoulder concept refers to transfer of occlusal loads to the bone when positioned below the bony crest and provides room for the bone over the implant, which provides support for the interdental papilla enabling esthetic gingival contours to be easily and consistently achieved. 4 The finite element method (FEM) refers to a numerical technique for structural analysis, which involves dividing a structure into simpler parts called finite elements. These finite elements are collectively known as mesh when assembled at the corner nodes.…”
Section: Introductionmentioning
confidence: 99%